The impact of different types of radiotherapy on cerebrovascular-specific death in patients with thyroid malignant tumors - Xianghong Wang; Xian Yang; Ruxin Wang; Chuanchuan Sun; Hongyun Lu (Discover Oncology)
Abstract Purpose The utilization of radiotherapy is a prevalent therapeutic intervention for thyroid malignancies, although its potential implications for cerebrovascular disease are still not comprehensively elucidated. Consequently, our objective was to explore the associated factors, particularly the additional influences, of radiotherapy on cerebrovascular mortality among individuals diagnosed with thyroid malignancies, in order to provide valuable clinical insights for management Methods In this study, we used the Surveillance, Epidemiology, and End Results (SEER) database to investigate the impact of radiotherapy on cerebrovascular death in patients diagnosed with thyroid malignancies, as well as to identify the factors that influence cerebrovascular death. To achieve this, we employed the COX proportional risk regression model for both single and multiple factor analysis to investigate the influence of various factors on cerebrovascular death. Additionally, we utilized propensity score matching (PSM) to adjust for confounding factors and minimize bias in baseline characteristics. Results Our study encompassed a cohort of 110,464 individuals who received a diagnosis of thyroid malignancies spanning the years from 1992 to 2019. Our meticulous analysis revealed that, prior to PSM, no significant association existed between radiation therapy (HR 0.906, 95% CI 0.750–1.095, p = 0.309] vs. no versus non-radiation therapy and the risk of cerebrovascular mortality in patients with thyroid malignant tumors. However, subsequent to PSM, the utilization of beam radiation (HR 2.034, 95% CI 1.121–3.692, p = 0.020) was discovered to confer an elevated risk of cerebrovascular mortality in patients diagnosed with thyroid malignancies, while other modalities of radiation therapy did not exhibit a statistically significant difference compared to non-radiation therapy. Furthermore, our investigation identified several noteworthy risk factors for cerebrovascular mortality, including advanced age at the time of diagnosis (HR 1.132, 95% CI 1.122–1.143, p < 0.001), male gender (HR = 1.347, 95% CI = 1.054–1.721, p = 0.017), African ethnicity (HR 1.813, 95% CI 1.152–2.854, p = 0.010), and Combined Summary Stage (distance) (HR 2.171, 95% CI 1.250–3.770, p < 0.006). Conclusion Our study results indicate that the additional impact of radiation on cerebrovascular outcomes varies among different types of radiation therapy. Specifically, “beam radiation” emerges as a significant risk factor for cerebrovascular mortality, while other radiation therapy methods do not appear to significantly increase this risk. These results particularly emphasize that patients with cerebrovascular risk factors (older age of diagnosis, Black ethnicity, male) should avoid beam radiotherapy methods. These results have important implications for clinicians as they can enable informed choice of appropriate radiotherapy for patients with thyroid malignancies, ultimately improving patient outcomes.